Observation of internal oxidation in a 20% cold-worked Fe-17Cr-12Ni stainless steel through high-resolution characterization. (December 2019) - Shen, Zhao; Tweddle, David; Lapington, Mark Thomas; Jenkins, Benjamin; Du, Donghai; Zhang, Lefu; Moody, Michael P.; Lozano-Perez, Sergio
Abstract: It is often assumed that internal oxidation cannot occur at temperatures below 400 °C. However, in the present work, internal oxidation was observed in a 20% cold-worked Fe-17Cr-12Ni stainless steel (SS) after exposure to simulated primary water of a pressurized water reactor at 340 °C and not in a similarly tested sample without prior cold-work. The formation of discrete Cr-oxide precipitates and the role of cold-work are discussed. The internal oxidation model is also proposed as a plausible stress corrosion cracking mechanism of Fe-17Cr-12Ni SS at that temperature. Graphical abstract: Unlabelled Image